2005
DOI: 10.1381/0960892052993549
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Gastric Stimulation Inhibits Gastric Motility via Sympathetic Pathway in Dogs

Abstract: Acute IGS inhibits postprandial antral contractions, and this inhibitory effect is mediated via the sympathetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…All recordings were displayed on a computer monitor. Motor activity of the stomach was assessed by using the mean area under the curve (AUC) per second, which was computed with the Polygram Function Testing Software (Medtronic) (52). The data presented in this study were obtained from channel 3, which had the highest quality recording.…”
Section: Recording and Analysis Of Antral Motilitymentioning
confidence: 99%
“…All recordings were displayed on a computer monitor. Motor activity of the stomach was assessed by using the mean area under the curve (AUC) per second, which was computed with the Polygram Function Testing Software (Medtronic) (52). The data presented in this study were obtained from channel 3, which had the highest quality recording.…”
Section: Recording and Analysis Of Antral Motilitymentioning
confidence: 99%
“…However, some investigators noted a role of sympathetic pathways in the effects of GES on gastrointestinal functions. The intravenous administration of guanethidine, an adrenergic blockade, prevents the inhibitory effect of GES on antral motility and rectal tone, indicating that GES effects are mediated via sympathetic adrenergic nerve activation (Zhu and Chen 2005;Liu et al 2005). Long-pulse retrograde GES at a tachygastrial frequency suppresses postprandial antral contractions via alpha-and beta-adrenergic pathways (Ouyang et al 2005).…”
Section: Afferent Pathwaysmentioning
confidence: 99%
“…For example, GES significantly inhibits postprandial antral contractions. Guanethidine, an adrenergic blocker, can prevent this effect of GES, suggesting involvement of sympathetic pathways (Zhu and Chen 2005). Intravenous injections of propranolol or phentolamine is reported to abolish long-pulse GES-induced tachygastria and antral hypomotility via the alphaand beta-adrenergic sympathetic pathways (Ouyang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of vagal activity with an advanced spectral analysis of heart rate variability indicates that effects of GES with certain parameters are relevant to increased vagal activity and accelerated gastric emptying in dogs and rats (Liu et al 2004;Ouyang et al 2003). Furthermore, intravenous administration of an adrenergic blocker prevents the inhibitory effect of GES on antral motility and/or rectal tone, indicating an involvement of the sympathetic adrenergic nerve fibers (Zhu and Chen 2005;Liu et al 2005;Ouyang et al 2005). The present study showed that vagotomy did not significantly affect the effects of GES on spinal neuronal activity but intravenous RTX abolished responses to GES in rats with vagotomy.…”
Section: Afferent Pathwaysmentioning
confidence: 99%
“…In rats, GES can activate vagal afferent fibers innervating the stomach (Peles et al 2003) and modulate activity of neurons in the nucleus tractus solitarii receiving gastric vagal afferents (Qin et al 2005). A few recent studies further suggest that effects of GES with varying parameters on gastric motility involve the sympathetic alpha-and beta-adrenergic sympathetic efferent pathways system (Zhu and Chen 2005;Ouyang et al 2005). The spinal sympathetic afferent pathways and the intraspinal neuronal activity relevant to GES effects also have been characterized recently in rats (Qin et al 2007).…”
Section: Introductionmentioning
confidence: 99%